Autoestima y toma de decisiones en adolescentes, Institución Educativa Zoila Hora de Robles - Chepén - González Lezcano, Luz Aurora (2019)
This research is kind of descriptive correlational and of transversal cut, it has made at the Educational Institution “Zoila Hora de Robles”- District of Chepén, with the purpose of determining the relation between the level of self-esteem and the making decision level in teenagers. The sample consisted of 102 teenagers. For the data collection, two instruments have used: Coopersmith Self-Esteem Inventory (1981) and the Ministry of Health Test Decision Making (2005), that were modified by González, Vilca and Villanueva (2017). The information which was obtained was processed and presented in statistical tables, for the analysis of the relationship between variables has used the statistical test "Pearson correlation". The following conclusions were reached: 52 percent of the adolescents presented average selfesteem, 47 percent presented hight self-esteem and 1 percent presented low self - esteem; 71 percent, presented a high making decisions level, 28 percent presented an average making decision level and 1 percent presented low making decision level. Have found a high level of significance (p=0.00) between variables was found.